So You Think You Can ELF: English as a Lingua Franca as the Medium of Instruction - Björkman, Beyza (HERMES - Journal of Language and Communication in Business, 2010)
This paper reports the ﬁndings of a study on spoken English as a lingua franca (ELF) in Swedish higher education. The aim has been to investigate the role pragmatic strategies play in content lectures where English is a lingua franca, i.e. a vehicular language. The ﬁndings show that lecturers in ELF settings make less frequent use of pragmatic strategies than students, who deploy these strategies frequently in group-work projects. Earlier stages of the present study showed that despite frequent non-standardness at the morphosyntax level, there is very little overt disturbance in student group-work (Björkman 2008a and b/2009b), most likely owing to a variety of communicative strategies used during interaction and the questions raised (Björkman 2009a). It seems reasonable to assume that, in the absence of appropriate strategies and questions that serve as real-time signals of disturbance, there is an increased risk for covert disturbance in lectures. This view complies with the ﬁndings of earlier studies on the importance of such strategies (Mauranen 2006, Airey 2009, Hellekjær 2010). The ﬁndings imply that the effectiveness of a speaker of English in academic ELF settings is determined primarily by the speaker’s pragmatic ability and less by his/her proﬁciency. There are important implications of these ﬁndings for lecturers who need to operate in ELF settings. First, increasing interactivity by using pragmatic strategies sufﬁciently frequently appears critical for those involved in English-medium education. It is also important that awareness is raised on target language usage in lecturing in English. Such awareness-raising can be achieved at the macro level by clearly-written language policies that include training for teachers and students who both need to be equipped with the skills needed to cope with the complexities of such settings, and at the micro level, by in-house training and courses that could be administered to both teachers and students.